Network optimization 5th International Conference, INOC 2011, Hamburg, Germany, June 13-16, 2011 : proceedings - INOC 2011 (Conferência) (Lectures notes in computer science)
This book constitutes the refereed proceedings of the 5th International Conference on Network Optimization, INOC 2011, held in Hamburg, Germany, in June 2011. The 65 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers highlight recent developments in network optimization and are organized in the following topical sections: theoretical problems, uncertainty, graph theory and network design; network flows; routing and transportation; and further optimization problems and applications (energy oriented network design, telecom applications, location, maritime shipping, and graph theory).